The effect of autologous bone marrow-derived stem cells with estimation of molecular events on tooth socket healing in diabetic rabbits (Histological and histomorphometric study) - Mohamed A Mohamed; Wasan H Younis; Nahi Y Yaseen (College of Dentistry/ University of Baghdad, 2014)
Background: Diabetes is a metabolic disorder characterized by chronic hyperglycemia due to an inability to produce insulin. Uncontrolled or poorly controlled diabetes is clinically associated with increased susceptibility to delay healing. Many recent researches have shown that stem cell therapy can be the best choice for treatment of this disease. The aims of this research were investigating regeneration of pancreatic beta cells of diabetic induced rabbits after stem cell transplantation. Materials and Methods: 64 rabbits weighting an average of (2.5 - 3 kg) were used in this experimental study, and divided into 4 groups as follows; group A ( contains 16 healthy rabbits regarded as control group ) , Group B ( contains 16 diabetic rabbits not received treatment ), group C ( contains 16 controlled diabetic rabbits received insulin as a treatment ) and group D ( contains 16 rabbits received mesenchymal stem cells as a treatment) , the lower incisor for each rabbits was extracted and the socket was examined by histological and histomorphometric analysis after 2, 10, 20 and 30 days of healing periods after scarification. Results: Histological findings showed that there was a normal healing of teeth extracted sockets (early bone formation, mineralization and maturation) of the animals of group A, C and D when compared with group B. Histomorphometric analysis of the parameters (trabecular width (TbW), Tb Separation(TbS), Tb Number ( TbNo), osteoblasts number (OBNo), osteocytes number( OCNo ) and blood vessels number (BVNo) of all groups for all healing periods illustrated that there was a highly significant differences of groups A , C and D when compared with group B animals. Conclusions: The present study concluded that there was delayed healing of teeth extracted sockets of the animals of group B (diabetic rabbits) due to the few numbers of osteoblasts (bone-forming cells) which differentiated from the fibroblasts cells and subsequent impairments in bone formation, mineralization and maturation.